2021
DOI: 10.1007/s00068-021-01832-8
|View full text |Cite
|
Sign up to set email alerts
|

Revision rate is higher in patients with periprosthetic femur fractures following revision arthroplasty in comparison with ORIF following our algorithm: a two-center 1 analysis of 129 patients

Abstract: Purpose Effective therapy of periprosthetic femur fractures of the hip (PPF) are challenging due to patients’ frailty and complexity of fracture patterns. The aim of this cohort study was to analyze the radiological and functional outcome following PPF. Methods A retrospective, multicenter study in the period 2009–2019 of patients with PPF at two level I trauma centers in Germany was performed. PPF were classified according to the Vancouver classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Many studies have reported noninferior outcomes of ORIF for management of B2 PFFs, with the advantage of a shorter operating time, lower blood transfusion rate, and overall fewer complications 26 48) . For example, ORIF, which can preserve the existing implant and provide good functional outcomes, may be preferred in treatment of stable B2 fractures with a good bone stock and minimal implant loosening 49 50 51) . Thus, there is potential for selection bias in the included studies reporting outcomes of ORIF in Vancouver B2 PFFs 44 45 46) .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported noninferior outcomes of ORIF for management of B2 PFFs, with the advantage of a shorter operating time, lower blood transfusion rate, and overall fewer complications 26 48) . For example, ORIF, which can preserve the existing implant and provide good functional outcomes, may be preferred in treatment of stable B2 fractures with a good bone stock and minimal implant loosening 49 50 51) . Thus, there is potential for selection bias in the included studies reporting outcomes of ORIF in Vancouver B2 PFFs 44 45 46) .…”
Section: Discussionmentioning
confidence: 99%